2012
DOI: 10.1111/j.1741-3729.2011.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Paradox of Empowerment” in Parent Education: A Reflexive Examination of Parents' Pedagogical Expectations

Abstract: In an action research project designed to develop a new paradigm for parent education in alignment with the “strengths perspective,” a social constructionist epistemology, and the empowerment discourse, it was found that parents joining two parent groups actually valued and sought expert knowledge. Seeking to empower these parents by adopting a collaborative learning approach—facilitating a reflective discussion of their parenting experience while refraining from meeting their expectation to be taught—we were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Understand that the identity transformation are accompaniments of deep, relational learning (Walters, 2008); . Co-constitute the reflexive identities with participants in the way that result in them having more expanded personal narratives and interpretations (Lam & Kwong, 2012); and . Create a mutually supportive environment in which the participants can open their minds to listen to others' stories and give one another genuine and inspiring feedback.…”
Section: The Programmentioning
confidence: 99%
“…Understand that the identity transformation are accompaniments of deep, relational learning (Walters, 2008); . Co-constitute the reflexive identities with participants in the way that result in them having more expanded personal narratives and interpretations (Lam & Kwong, 2012); and . Create a mutually supportive environment in which the participants can open their minds to listen to others' stories and give one another genuine and inspiring feedback.…”
Section: The Programmentioning
confidence: 99%
“…Research has shown that parenting training can damage parents' confidence or alienate those who feel patronized (Todd and Higgins 1998). In addition, the idea that the practitioner possesses some sort of superior knowledge to that which the parent possesses may only perpetuate the power imbalance in the relationship between professionals and parents (Lam and Kwong 2012;Safford and Safford 1996). For parents, being a recipient of the practitioner's knowledge and skills-training may be interpreted as their giving up their own values and beliefs with respect to parenting.…”
Section: Breaking Down the Walls Between Social Workers And Parents: mentioning
confidence: 99%
“…A review of the development of parent education in Hong Kong reveals that parent education is commonly offered by parent education practitioners who impart parenting knowledge and skills to parents through various parent education programs, which aim to promote positive physical, intellectual, psychological, and social development of children [1,20,21]. Nevertheless, in their assessment of the existing mode of service provision, Chan [5], Lam [1], Lam and Kwong [2], Leung and Lam [3], and To and Chan [4] comment that parent education programs in Hong Kong are rather problem-focused. It is observed that parents are mainly helped to confront the problems of their children and themselves.…”
Section: The Significance Of Addressing Parents' Existential Concernsmentioning
confidence: 99%
“…The current social concerns over parenting in Hong Kong have serious implications for rethinking the direction of parent education [1][2][3][4]. Under the present dominant ideology of parent education, people tend to focus on the predicaments surrounding families while neglecting the opportunities embedded in parenthood for enhancing life advancement, strengths and possibilities for parents to seek positive changes [5,6].…”
Section: Introductionmentioning
confidence: 99%